Wandering and exile in soul music: the Black-Rio movement in the 70’s to the Quarteirão do Soul in Belo Horizonte, 2010 (Tempo e Argumento, 2010)
The twentieth century witnessed several diasporas. Some of them clearly addressed by the vehicles of mass communication, others less so. This study addresses the emergence of a movement of affirmation of black identity in Brazil, the movement Black-Rio, which appeared in the mid-70s. It suffered persecution, not only on the political side, but also from the media, until its extinction in the same decade. The importance of the Black-Rio was confirmed thirty years later, with the constitution of the Quarteirão do Soul in Belo Horizonte, a movement with similar ideology. It started downtown in 2004 with a group of friends, became a space of sociability and affirmation of black identity and, like its predecessor, begins to suffer harassment.
Keywords: Soul music; back identity; mass culture